Dampak Pasca Pandemi Covid-19 Terhadap Bisnis Hotel Ciputra Cibubur - Rizki Nugraha; Achmad Salam (Jurnal Ilmiah Wahana Pendidikan, 2023)
The pandemic that began to spread in the new year 2020 greatly affected the economy, including the Cibubur Ciputra Hotel. PHRI recorded nearly 40,000 cancellations of hotel rooms with a total loss of IDR 1 trillion. The purpose of this study was to try to identify strategies for handling and improving the quality of the Ciputra Cibubur Hotel after the Covid-19 pandemic. The analysis techniques in this study were interview and observation approaches. Based on the interviews conducted, it was found that the strategy for handling the Ciputra Cibubur Hotel after the Covid-19 pandemic was quite good and the quality of the services provided was quite good and its implementation must be improved to provide confidence and a sense of security to guests and the recommendations given are to innovate, adapt and collaboration in improving the marketing and service quality of Hotel Ciputra Cibubur after the covid 19 pandemic.